Perceptions of the prehistoric in Anglo-Saxon England religion, ritual, and rulership in the landscape - Semple, Sarah 1973- (Medieval history and archaeology, 2014)
This title represents an unparalleled exploration of the place of prehistoric monuments in the Anglo-Saxon psyche, and examines how Anglo-Saxon communities perceived and used these monuments during the period AD 400-1100